O touro da necrópole de Cinco Reis 8 (Beringel, Beja, Portugal) - Arruda, Ana Margarida (2016)
The archaeological excavations carried out in the Iron Age necropolis Vinha das Caliças (Beja, Portugal) offered a terracotta piece representing a bull. Their morphological characteristics, but also the general context and more specifically the fact that it was collected in one section of the pit demarcating the funerary space had implied a discussion according to the funeral rites, but also focused in it’s religious significance in the aim of cult practices, strongly influenced by the presence of Mediterranean communities in the Iberian Peninsula from the 8th c. B.C.